When sepsis persists: a review of MRSA bacteraemia salvage therapy. (12th November 2015) - Kullar, Ravina; Sakoulas, George; Deresinski, Stan; van Hal, Sebastiaan J.
Abstract: MRSA bacteraemia (MRSAB), including infective endocarditis, carries a high mortality rate, with up to 50% of patients failing initial therapy with vancomycin and requiring salvage therapy. Persistent MRSAB can be difficult to successfully eliminate, especially when source control is not possible due to an irremovable focus or the bacteraemia still persists despite surgical intervention. Although vancomycin and daptomycin are the only two antibiotics approved by the US FDA for the treatment of patients with MRSAB as monotherapy, the employment of novel strategies is required to effectively treat patients with persistent MRSAB and these may frequently involve combination drug therapy. Treatment strategies that are reviewed in this manuscript include vancomycin combined with a β-lactam, daptomycin-based therapy, ceftaroline-based therapy, linezolid-based therapy, quinupristin/dalfopristin, telavancin, trimethoprim/sulfamethoxazole-based therapy and fosfomycin-based therapy. We recommend that combination antibiotic therapy be considered for use in MRSAB salvage treatment.